Green Sea Turtle, Chelonia mydas (Linnaeus 1758) Conservation in Lundu, Sarawak: Historical Perspective, Framework for Headstart and Community-based Effort: - Nurhartini Kamalia, Yahya (Universiti Malaysia Sarawak, (UNIMAS), 2018)
Green turtle exists in Sarawak waters and its small scale conservation effort had already started since 1950s. The success of the effort is still debatable, as the data collected was not made readily available, while public participation in the conservation effort is still at infancy stage. The current study involved analysing nesting data of green turtles of Sarawak Turtle Islands, headstarting to obtain survival and growth of turtles in captivity while predicting the size at maturity for Sarawak’s green turtle, disease profiling of turtle carcass from headstart program and conducting community based awareness program. Nesting, egg collection, incubation and hatching success data for 36 years has shown that Sarawak’s green sea turtle population has stabilized (approximately 3000 nesters) after the drop in nesting trend in the 1950s. The number of eggs collected and incubated since 1990 until 2016 was 90 to 100 %, which helped to improve the number of nesters as more hatchlings were released into the sea. Estimation shows that Sarawak has an average of 3,088 mature nesters from 2010 until 2016 that corresponds to a calculated remigration interval of 3 to 4 years with internesting frequency of 3 times per season for matures nesters. Eighteen months of headstart program has been successful with survival rate of 22.5 % and 82 % for Batch 1 and 2, respectively. The growth rate of the turtles was 9.86 cm/year (Batch 1) and 15.92 cm/year (Batch 2). Batch 2 was found to be heavier and longer compared to Batch 1 with mean of 2.65 ± 0.64 g for weight and mean of 2.16 ± 0.02 cm for straight carapace length (SCL) compared to Batch 1’s mean of 2.51 ± 0.63 g for weight and mean of 2.08 ± 0.19 cm for SCL. Based on both growth data from the headstart program and secondary data, a von Bertalanffy growth function was obtained for green turtles of Sarawak, where a first time female nester in 1982 with SCL of 101.03 cm was estimated to be between 12.5 to 13 years old. Commonly observed physical appearances of dead hatchlings were eye infection, bite mark, red or blue marks, bloated plastron and emaciation. The types of diseases found were classified as infectious and non-infectious. The commonly found bacteria that are associated with infectious diseases are Proteus sp., Pseudomonas sp., Klebsiella pneumonia, Morganella morganii and Citrobacter freundii while 4 taxa of fungi namely Cladosporium spp., Penicillium sp., Aspergillus spp. and Gibberella sp. were found in the carcasses. Batch 1 showed a higher disease and mortality count when compared to Batch 2 as the handling and management technique was better for the latter. A Standard Operating Procedure comprising of human-turtle interaction manual, husbandry practice plus behavioural and disease management tactics to be used for small scale headstart program was produced. The awareness programs resulted in a positive community-based effort involving local communities of Lundu, the public, as well as private and government agencies. Development of an educational toolkit on green sea turtle at the end of the project is hoped to be of help in the conservation of sea turtle in the future. The survey conducted during the program has reflected a positive vibe as 96.5 % of the total participants were willing to attend another sea turtle awareness program.